Influence of the Mass Rapid Transit System on Plotted Residential Property Prices: A Case Study of Gurugram, India - Fandian, Sneh; Panwar, Manoj (Journal of Contemporary Urban Affairs, 2025)
Mass Rapid Transit Systems (MRTS) are increasingly recognised as critical drivers of urban transformation, particularly in rapidly urbanising cities at the Global level.  However, empirical research on their influence on plotted residential property markets in emerging urban contexts remains limited. This study investigates the socio-economic impact of the Delhi Metro Line extension in Gurugram, India, across the various phases of the metro project. Using a mixed-methods approach, it combines a hedonic price modelling of 300 residential properties from 2007 to 2024 with qualitative surveys and spatial analysis. The study measures "proximity premiums" and contextualises them through stakeholder perspectives. The results indicate that properties within 500 metres of a metro station experienced price growth of 20–25% after project announcement and around 30% post-operation, relative to earlier trends. These effects are highly localized, with premiums diminishing beyond 1km and disappearing beyond 1.5-2km. The hedonic model confirmed distance to the nearest station as a key determinant of price with an average 12% price decrease per kilometre (p < 0.01), along with other influential variables like plot size, proximity to the CBD, and highway access. The model showed strong explanatory power (R² ≈ 0.64). The findings reveal that MRTS can substantially enhance residential property prices but also influence the spatial distribution of economic opportunities, potentially intensifying socio-economic disparities if unregulated. This paper advances the debate on land value capture in Indian cities, offering evidence-based recommendations for equitable urban development strategies in the context of contemporary urbanisation.